Surface Modification of a Graphite Felt Cathode with Amide-Coupling Enhances the Electron Uptake of Rhodobacter sphaeroides - Hana Nur Fitriana; Jiye Lee; Sangmin Lee; Myounghoon Moon; Yu Rim Lee; You-Kwan Oh; Myeonghwa Park; Jin-Suk Lee; Jinju Song; Soo Youn Lee (Applied Sciences, 2021)
Microbial electrosynthesis (MES) is a promising technology platform for the production of chemicals and fuels from CO2 and external conducting materials (i.e., electrodes). In this system, electroactive microorganisms, called electrotrophs, serve as biocatalysts for cathodic reaction. While several CO2-fixing microorganisms can reduce CO2 to a variety of organic compounds by utilizing electricity as reducing energy, direct extracellular electron uptake is indispensable to achieve highly energy-efficient reaction. In the work reported here, Rhodobacter sphaeroides, a CO2-fixing chemoautotroph and a potential electroactive bacterium, was adopted to perform a cathodic CO2 reduction reaction via MES. To promote direct electron uptake, the graphite felt cathode was modified with a combination of chitosan and carbodiimide compound. Robust biofilm formation promoted by amide functionality between R. sphaeroides and a graphite felt cathode showed significantly higher faradaic efficiency (98.0%) for coulomb to biomass and succinic acid production than those of the bare (34%) and chitosan-modified graphite cathode (77.8%), respectively. The results suggest that cathode modification using a chitosan/carbodiimide composite may facilitate electron utilization by improving direct contact between an electrode and R. sphaeroides.